1990
DOI: 10.1002/j.1537-2197.1990.tb13553.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of Fern Spore Proteins: Globulin Storage Proteins in Onoclea Sensibilis and Osmunda Cinnamomea

Abstract: Onoclea sensibilis was found to contain globulin storage proteins of 2.0S and 11.3S. These globulins, comparable in size and subunit composition to the spore storage proteins characterized in Matteuccia struthiopteris (Templeman, DeMaggio, and Stetler, 1987), declined during imbibition and the initial stages of spore germination. Osmunda cinnamomea, a fern that is only distantly related to Matteuccia, also contained globulin proteins, but these had S values of 5.5 and 11.3. SDS-PAGE analysis revealed extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Intron D was not found among all angiosperms [28], while the absence of both intron A and intron C is a unique situation for Welwitschia mirabilis, a representative of Gnetales [29]. Shutov and Bäumlein [28] speculated that the D/B-like intron is an ancient feature of the storage globulin single-domain ancestor, which predates its duplication [35]. According to those authors, introns C and A might be considered as later events, which occurred independently after duplication.…”
Section: Evolutionary Relationships Of Buckwheat Leguminsmentioning
confidence: 97%
“…Intron D was not found among all angiosperms [28], while the absence of both intron A and intron C is a unique situation for Welwitschia mirabilis, a representative of Gnetales [29]. Shutov and Bäumlein [28] speculated that the D/B-like intron is an ancient feature of the storage globulin single-domain ancestor, which predates its duplication [35]. According to those authors, introns C and A might be considered as later events, which occurred independently after duplication.…”
Section: Evolutionary Relationships Of Buckwheat Leguminsmentioning
confidence: 97%
“…Together these results show that SSPs are highly conserved in plants and were present in a common ancestor prior to the divergence of angiosperms and gymnosperms some 300-350 MYR ago [16,18]. It would be of interest to see whether additional similarities also exist in the storage polypeptides of fern spores [ 17]. Such data would further expand our understanding of the evolution of SSPs, and in addition, could provide useful outgroup data for phylogenetic studies using S SP sequences.…”
Section: Sss 448 Spruce S G G H E E R E Q E E E E R E E R H G G R G Ementioning
confidence: 99%
“…More recent studies have shown that fern spores contain two major groups of storage proteins corresponding to the I I S legumins and 2-3s albumins of flowering plants (DeMaggio & Stetler, 1980;Templeman et al, 1987;Conant & DeMaggio, 1989;Templeman & DeMaggio, I 990). However, of greater interest are the 2s albumins, which are major components of Onoclea (Templeman & DeMaggio, 1990) and Matteuchia (Templeman et al, 1987; but not Osmunda, which contains a 5'5s albumin/globulin (Templeman & DeMaggio, I 990). However, of greater interest are the 2s albumins, which are major components of Onoclea (Templeman & DeMaggio, 1990) and Matteuchia (Templeman et al, 1987; but not Osmunda, which contains a 5'5s albumin/globulin (Templeman & DeMaggio, I 990).…”
Section: Spore Storage Proteins Of Bryophytes and Pteridophytesmentioning
confidence: 99%
“…Onclea sensibilis, Osmunda cinnamomea and Matteuchia struthropteris all contain globulins of SaOw = I 1.3 S, which are considered to be legumin-like on the basis of their amino acid composition, solubility, and subunit composition and properties (Templeman et al, 1987). However, of greater interest are the 2s albumins, which are major components of Onoclea (Templeman & DeMaggio, 1990) and Matteuchia (Templeman et al, 1987; but not Osmunda, which contains a 5'5s albumin/globulin (Templeman & DeMaggio, I 990). The 2.2s albumin of Matteuchia (termed matteuchin) consists of two subunits of Mr about 8000 and 3000, which are linked by disulphide bonds.…”
Section: Spore Storage Proteins Of Bryophytes and Pteridophytesmentioning
confidence: 99%